Penggunaan Crazy Story Game untuk Meningkatkan Motivasi Mahasiswa Berbicara dalam Bahasa Inggris - Nurdiana Nurdiana (Departemen Bahasa dan Sastra Indonesia dan Daerah, 2020)
Various ways and efforts have provided by Speaking lecturers to increase students’ motivation, especially in Speaking. However, based on a preliminary study, researchers found that students' speaking motivation was still considered insufficient. For that, the researcher applied a game, namely Crazy Story. The purpose of this study was to see how students’ motivation who were taught and not taught using Crazy Story Game and to find out whether there was a significant difference between students’ motivation who were taught and not taught using Crazy Story Game. This research was an experimental research. This type of research was a quasi-experimental study using an unequal group design. This study consisted of two groups, namely experimental and control group. The population of this study were students of the third semester of the English Education Study Program. Two groups (classes) of students consisted of 60 people were taken as samples using cluster random sampling. The two groups of students were both given a questionnaire to see their motivation in speaking before and after implementing Crazy Story Game. The data collection techniques were questionnaire and observation. Questionnaire was used to determine students’ motivation in speaking English. Meanwhile, observation was used to see the learning process of Speaking by using Crazy Story Game. From the research findings, it was obtained that the Speaking Motivation data of students who joined the experimental class increased by 4.75%. Meanwhile, students’ speaking motivation who joined the control class only increased by 0.98%. The result of data analysis from T-test was 2.028. This result was compared with the t table with a df (Degree of Freedom) level of 78, namely 1.99. Because t count t table (2.028 ≥ 1.99) and the significance was (0.046 0.05), H0 was rejected and Ha was accepted. The researcher concluded that there was a significant difference between students’ motivation those who were taught and not taught using Crazy Story Game.